Critical appraisal of diagnostic laboratory tests in the evaluation of central precocious puberty - Bangalore Krishna, Kanthi; Garibaldi, Luigi (Frontiers in Pediatrics, 2025)
Pubertal onset is characterized by reactivation of the hypothalamic-pituitary-gonadal axis resulting in pulsatile gonadotropin secretion and subsequent sex steroid production. An accurate measurement of the gonadotropins and sex steroids are essential to ensure timely diagnosis of precocious puberty, so as to determine optimal management. This review summarizes the available laboratory testing for the diagnosis of puberty, discussing the different assays used while reviewing the limitations of such testing.